2012
DOI: 10.3109/17435390.2011.648224
|View full text |Cite
|
Sign up to set email alerts
|

Heme oxygenase expression as a biomarker of exposure to amphiphilic polymer-coated CdSe/ZnS quantum dots

Abstract: Because of their unique optical properties quantum dots (QDs) have become a preferred system for ultrasensitive detection and imaging. However, since QDs commonly contain Cd and other heavy metals, concerns have been raised regarding their toxicity. QDs are thus commonly synthesized with a ZnS cap structure, and/or coated with polymeric stabilizers. We recently synthesized amphiphilic polymer coated TOPO-PMAT QDs which are highly stable in aqueous environments. The effects of these QDs on viability and stress … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
28
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 22 publications
(31 citation statements)
references
References 59 publications
3
28
0
Order By: Relevance
“…There was essentially no change in cell membrane integrity using Trypan Blue for all three PDots (Figure 3, panel B), while the positive control with 0.2nM Etoposide showed a 30% decrease. These results indicated that PDots do not substantially affect cell viability for doses ranging from 2.5 nM to 40 nM, which is consistent with previously reported results 10,19-21,22 and are comparable to those of QDots previously reported as well 24 .…”
Section: Resultssupporting
confidence: 92%
See 3 more Smart Citations
“…There was essentially no change in cell membrane integrity using Trypan Blue for all three PDots (Figure 3, panel B), while the positive control with 0.2nM Etoposide showed a 30% decrease. These results indicated that PDots do not substantially affect cell viability for doses ranging from 2.5 nM to 40 nM, which is consistent with previously reported results 10,19-21,22 and are comparable to those of QDots previously reported as well 24 .…”
Section: Resultssupporting
confidence: 92%
“…with in vivo exposures. RAW264.7 cells were previously reported to show good uptake capability for QDots 24 . In this study, RAW264.7 cells avidly took up both QDots and PDots as shown in Figure 2.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Pulmonary HO-1 levels were reported to be an effective marker of oxidative stress (Ayres et al, 2008;Li et al, 2009), and prior in vitro research indicated HO-1 as a biomarker of exposure to quantum dot nanoparticles, which elicit their acute toxicity via generation of reactive oxygen intermediates (McConnachie et al, 2013). Further, evidence from in vivo studies utilizing chronic UF ambient particle exposure demonstrated activation of the Nrf-2 signaling pathway, a regulator of HO-1 and a pathway subject to diminished upregulation with aging that might potentially explain additional susceptibility in the aging population to PM pollution (Zhang et al, 2012).…”
Section: Discussionmentioning
confidence: 99%